PENGEMBANGAN MULTIMEDIA INTERAKTIF MATA PELAJARAN IPA KELAS IVC SD NEGERI 034 TARAIBANGUN KABUPATEN KAMPAR - Mizana Qistina; Mahmud Alpusari; Eddy Noviana; Neni Hermita (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
This study aims to develop interactive multimedia learning media on science subjects using Adobe Flash as a learning media for SD IVC classes. This development is in the form of learning media products in an interactive CD. The method used in this study uses the Research and Development (R & D) method with a 4D model that has 4 stages of development, namely define, design, development, and desseminate. The results of the validation test show that interactive multimedia learning media in science subjects are declared good with the results of validation by media experts 3.75 with very valid categories, expert material 3.5 with very valid categories, and by 3.54 users in good categories. Based on the N-Gain of 0.60 with the medium category and it can be said that the effectiveness of interactive multimedia as a learning media is classified as effective. Based on these results, it can be concluded that the development of interactive multimedia on science subjects using adobe flash as an instructional media for SD IVC is declared feasible and effective to be used in the learning and teaching process